Replenished microglia partially rescue schizophrenia-related stress response - Yan, Ling; Xuan, Fang-Ling; Chen, Song; Gou, Mengzhuang; Chen, Wenjin; Li, Yanli; Wang, Zhiren; Wang, Leilei; Xie, Ting; Fan, Fengmei; Zharkovsky, Alexander; Tan, Yunlong; et al. (Frontiers in Cellular Neuroscience, 2023)
Background: Microglia play an important role in maintenance of brain and behavioral homeostasis. Protective effect of microglial replenishment was reported in neurological diseases, but whether microglial therapy would benefit psychiatric disorders such as schizophrenia has been unclear. As schizophrenia is a stress-vulnerable disorder and psychosocial stress promotes inflammation and microglial activation, we aim to understand how microglial replenishment works in stress-associated schizophrenia. Methods: We used a CSF1R-mediated pharmacological approach to study repopulated microglia (repMg) in a cohort of mice (n=10/group) undergoing chronic unpredictable stress (CUS). We further studied a cohort of first-episode schizophrenia (FES, n=74) patients who had higher perceived stress scores (PSS) than healthy controls (HC, n=68). Results: Reborn microglia attenuated CUS-induced learned hopelessness and social withdrawal but not anxiety in mice. Compared to control, CUS- or repMg-induced differentially expressed genes (DEGs) in the prefrontal cortex regulated nervous system development and axonal guidance. CUS also caused microglial hyper-ramification, and increased engulfment of synaptophysin and vesicular glutamate transporter-2 by microglia and astrocytes, which were recovered in CUS+repMg (all p<0.05). Moreover, FES patients had smaller hippocampal fimbria than HC (p<1e-7), which were negatively associated with PSS (r=-0.397, p=0.003). Blood DEGs involved in immune system development were also associated with PSS and the right fimbria more prominently in FES than HC (Zr, p<0.0001) and KCNQ1 was a partial mediator between PSS and fimbria size (=-0.442, 95% CI: -1.326~-0.087). Conclusion: Microglial replenishment may potentially benefit psychiatric disorders such as schizophrenia.